Early age strength enhancement of blended cement systems by CaCl2 and diethanol-isopropanolamine - Riding, Kyle A.; Silva, Denise A.; Scrivener, Karen (My University, 2010)
The enhancement of the 1 day strength of cementitious systems by a combination of calcium chloride (CaCl2) and diethanol-isopropanolamine (DEIPA) was studied, particularly in blended cement systems. A combination of quantitative X-ray diffraction with Rietveld refinement (QXRD), scanning electron microscopy (SEM)/ backscattered electron image analysis, thermogravimetric analysis (TGA), and isothermal calorimetry were used to investigate the mechanism of strength enhancement by the additives. The additives were found to increase the early age mortar strength by enhancing the cement hydration, with the DEIPA enhancing primarily the aluminate hydration. DEIPA also affected the morphology of portlandite which was formed as thin plates. In parallel, the calcium-to-silica ratio of the C-S-H was found to increase with the use of DEIPA, possibly because of the inclusion of microcrystalline portlandite. After 48 hours DEIPA was found to directly enhance the rate of reaction of granulated blast-furnace slag and fly ash.
Keywords: Acceleration; Microstructure; Granulated Blast-Furnace Slag; Fly Ash